To fill in the blanks and factor the expressions based on your provided number bank, here are the answers for each expression:
-
x² = () ()
The quadratic expression x² can be factored as:
x² = (x)(x)So, the answer is:
x² = (x)(x) -
3x = __9 (x² − 2x + 3)
To factor 3x with respect to 9(x² - 2x + 3), we can identify the coefficient needed. Since 3x is equal to 3 multiplied by something, we need to find how to write 3 as a factor of 9. To do this, we can match coefficients. So:
3x = 1 × 9 (x² - 2x + 3)The answer is:
3x = 1 9 (x² - 2x + 3) -
9x = () () + 5
To express 9x in terms of a product along with 5, we can express it as:
9x = 9 (x) + 5So, the answer is:
9x = (9)(x) + 5
In summary:
- x² = (x)(x)
- 3x = 1 9 (x² − 2x + 3)
- 9x = (9)(x) + 5